A converging path: a decade’s reflection on net zero emissions and the circular economy - Munir, Muhammad Tajammal; Naqvi, Muhammad; Li, Bing (Frontiers in Energy Research, 2024)
In the past decade, global sustainability efforts have increasingly focused on two critical paradigms: achieving net zero emissions (NZE) and advancing the circular economy (CE). This article provides a detailed examination of the challenges and breakthroughs in harmonizing these approaches, drawing from a broad range of academic discussions, technological innovations, policy developments, and practical implementations. We identify specific obstacles, such as technological limitations, policy inertia, and economic and social barriers, that hinder progress towards NZE and CE. The paper then outlines targeted solutions, including cutting-edge technologies like carbon capture and storage, policy frameworks that incentivize sustainable practices, and examples of successful circular economy models. Through a critical analysis of both the synergies and tensions between NZE and CE, the article highlights the necessity for cross-sector collaboration, robust policy support, and ongoing innovation to overcome these challenges. Concluding with a forward-looking perspective, we emphasize strategic pathways for integrated sustainability efforts, advocating for a multi-faceted approach that combines technological advancement, policy reform, and stakeholder engagement. By offering a more nuanced understanding of the interplay between theoretical goals and practical realities, this revised abstract aims to inspire action and foster a collective move towards a sustainable global future.